A DECISION-MAKING FRAMEWORK FOR OPTIMIZING HEAVY-EQUIPMENT DELIVERY VIA LANDING CRAFT TANK AT AN INDONESIAN MINING-LOGISTICS COMPANY - Vincent Saragossa Handa Prasetyo; Pri Hermawan (RADJA PUBLIKA, 2026)
Heavy-equipment delivery by Landing Craft Tank (LCT) is critical to mining operations in Indonesia’s archipelagic regions, yet routing decisions are often made without structured analytical support. This study develops a decision-making framework for optimizing LCT delivery at a mining-logistics company that relies predominantly on single-origin–single-destination (SOSD) voyages. Using a quantitative-dominant single-case design, 55 LCT voyages from 2025 (498 equipment-unit movements) were analysed through voyage-level key performance indicators—load factor, cost per ton, and cost per nautical mile. The Analytic Hierarchy Process (AHP) structured the choice between SOSD and multi-origin–multi-destination (MOMD) routing across six criteria, complemented by thematic analysis of seven expert practitioners and Failure Mode and Effects Analysis (FMEA). The fleet recorded a low mean load factor of 27.7%, with 54 of 55 voyages below 50%. The multi-stop voyages observed in practice were not cheaper than SOSD, indicating that consolidation alone does not guarantee savings. AHP ranked SOSD first (global priority 0.540 versus 0.460). The study contributes a managerially usable, data-driven framework integrating performance measurement, multi-criteria evaluation, and risk assessment to guide LCT routing decisions.